ORGANIZATION OF PHYSICAL EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Toshmatova Zamira Jumanovna (Galaxy International Interdisciplinary Research Journal, 2025)
This article considers the effective organization of physical education classes in preschool education not only to strengthen the physiological aspects of the children's body, but also to develop their mental potential, and to form social skills.